Examining The Influence Of Islamic Branding, Physical Evidence, And Relationship Quality On Customer Loyalty In The Context Of Bank Syariah Indonesia (BSI) Makassar Branch At Unismuh - Riady, Achmad; Farida, Ida; Husna, Mutammimal; Elvi, Elvi (Al-Makki Publisher, 2024)
This study aims to investigate the influence of certain factors on customer loyalty in using Bank Syariah Indonesia (BSI) KCP Makassar Unismuh products. The factors studied include Islamic branding, physical evidence, and relationship quality. The research was conducted from July to August 2023 using a descriptive quantitative approach. The data used in this study are primary data collected through the distribution of questionnaires, observation, and documentation. The sample of this study was selected by simple random sampling and consisted of 75 respondents. To analyze the data, this study used multiple linear regression and the SPSS version 20 application. The results showed that partially, Islamic branding has no significant effect on customer loyalty. However, physical evidence and relationship quality partially have a positive and significant influence on customer loyalty. Simultaneously, islamic branding, physical evidence, and relationship quality have a positive and significant effect on customer loyalty. The implications of this study indicate that factors such as Islamic branding, physical evidence, and relationship quality have a positive impact on customer loyalty in using BSI KCP Makassar Unismuh products. Although Islamic branding does not have a significant effect partially, other factors still make a good contribution to customer loyalty in using BSI products